Behavioral Effects of Systemic, Infralimbic and Prelimbic Injections of a Serotonin 5-HT2A Antagonist in Carioca High- and Low-Conditioned Freezing Rats - León, Laura A.; Castro-Gomes, Vitor; Zárate-Guerrero, Santiago; Corredor, Karen; Mello Cruz, Antonio P.; Brandão, Marcus L.; Cardenas, Fernando P.; Landeira-Fernandez, J. (Frontiers in Behavioral Neuroscience, 2017)
The role of serotonin (5-hydroxytryptamine [5-HT]) and 5-HT2A receptors in anxiety has been extensively studied, mostly without considering individual differences in trait anxiety. Our laboratory developed two lines of animals that are bred for high and low freezing responses to contextual cues that are previously associated with footshock (Carioca High-conditioned Freezing [CHF] and Carioca Low-conditioned Freezing [CLF]). The present study investigated whether 5-HT2A receptor blockade by the widely used preferential 5-HT2A receptor antagonist ketanserin exerts distinct anxiety-like profiles in these two lines of animals. In the first experiment, the animals received a systemic injection of ketanserin and were exposed to the elevated plus maze. In the second experiment, these two lines of animals received microinjections of ketanserin in the infralimbic and prelimbic cortices and were exposed to either the elevated plus maze or a contextual fear conditioning paradigm. The two rat lines exhibited bidirectional effects on anxiety-like behavior in the elevated plus maze and opposite responses to ketanserin. Both systemic and intra-infralimbic cortex injections of ketanserin exerted anxiolytic-like effects in CHF rats but anxiogenic-like effects in CLF rats. Microinjections of ketanserin in the prelimbic cortex also exerted anxiolytic-like effects in CHF rats but had no effect in CLF rats. These results suggest that the behavioral effects of 5-HT2A receptor antagonism might depend on genetic variability associated with baseline reactions to threatening situations and 5-HT2A receptor expression in the infralimbic and prelimbic cortices.